MULTIMEDIA SEBAGAI MEDIA PEMBELAJARAN FIQIH MENGGUNAKAN ADOBE FLASH CS5 - Tri Yusnanto; Moch Ali Mahmudir; Sugeng Wahyudiono (Journal of Professional Elementary Education, 2022)
Multimedia as a fiqh learning medium at MI Ma'arif Darussolihin Jonggrangan which can increase students' learning interest so as not to quickly feel bored in receiving lessons, to improve student learning achievements as expected, especially in fiqh subjects, considering that the results of student learning achievements are currently not as expected. Namely, the average class is 6.8, while the common value of competency of fiqh subjects that apply today is 7.7. Currently, the approach applied by teachers in fiqh learning still uses a conventional approach. The research method used by researchers is the waterfall model. They are designing a multimedia-based fiqh learning media MI Ma'arif Darussolihin Jonggrangan using the Action Script programming language. Design the system using Adobe Flash CS5 version 9.0 software and graphics processing, using Adobe Photoshop CS5 version 11.0 and Corel Draw X7 software. At the time of all the pretests obtained an average score of 38.95, and students were declared incomplete, while posttests got an average score of 81.4 with a proportion of 92.1% completion with the results of 35 students declared complete while three were declared incomplete. So that it can be said that the application of learning media in the study of fiqh can improve student learning outcomes. The results of this study are a multimedia-based fiqh learning medium that can help solve problems about student achievement results that have not been in line with expectations